Décadence urbaine et Hors-la-loi sexuels dans l’univers de Blade Runner - Robert Yeates (ReS Futurae)
The urban future of Los Angeles in Ridley Scott’s film Blade Runner (1982) is one of advanced decay, an sf-noir vision of a postwar metropolis in decline. While the city falls into profound disrepair and its citizens succumb to debilitating sicknesses, however, the furor over fugitive replicants consumes the attentions of the authorities and the blade runner protagonists. The film and the 1997 video game based upon it take a novel set in San Francisco, the home of some of the first gay neighborhoods in the US that suffered from the crackdowns of the late 1970s and 1980s, and transplants this to Los Angeles, a city which glamorized decay, adding an aesthetic that draws on the look of New York, a city notoriously in economic decline in the 1970s. The plight of specials, replicants, and blade runners in the Blade Runner universe reflects the context of a culture fixated on the policing of arbitrary dividing lines separating what is designated sexually deviant or undesirable in American cities at the time.